Regional policy of the European Union as an institutional prerequisite for ensuring sustainable development of territories (Economics and region, 2025)
The article reveals the essence, content and significance of the regional policy of the European Union as an institutional prerequisite for ensuring sustainable development of territories in modern conditions of global transformations. The methodological basis of the study is the institutional, systemic, comparative and content-analytical approaches, which allowed to identify the structural and functional features of the EU regional policy, which is considered as a systemic mechanism for achieving a balance between economic efficiency, social cohesion and environmental safety, which is based on the principles of solidarity, subsidiarity, complementarity, partnership and multi-level governance. The evolution of cohesion policy is highlighted - from leveling regional disparities and supporting problem areas to modern priorities of digital, innovative and green transformation. The key issue, in the authors' opinion, was and remains the issue of finding the optimal balance between ensuring the competitiveness of the EU economy and its members and the need to equalize the level of development of regions. The institutional architecture and key financing instruments are described: the European Regional Development Fund, the Cohesion Fund, the European Social Fund+, the Just Transition Fund and the temporary NextGenerationEU instrument aimed at post-crisis recovery, modernisation of economies and achieving climate neutrality. It is noted that modern regional policy contributes to the implementation of the Sustainable Development Goals, supports innovation, human potential development, ensures inclusiveness and competitiveness of regions. The practical experience of Member States, in particular Poland, Spain, Italy, in using EU funds for regional development is summarized. The importance of adapting European mechanisms for Ukraine in the context of decentralisation, post-war recovery and integration into the European space is underlined. The need to form a national model of regional policy focused on sustainable development, social justice, environmental balance and effective management based on the principles of good governance is substantiated.
Keywords: European Union; Ukraine; sustainable development; regional policy; principles; institutionalization; innovations; economy; social sphere; ecology; public administration